Visual food recognition using artificial intelligence - Zhao, Heng (Nanyang Technological University, 2022)
Food-related research gains increasing attention for its importance in people's daily life. Proper understanding of daily food intake benefits not only individual's personal health but also the collective good of the society. Visual food classification is to recognize different food dishes from pictures. Early approaches of visual food classification focus on traditional classification methods that are based on hand-crafted image features. The more recent progress made in visual food classification uses various popular deep architectures such as convolutional neural networks (CNNs) and performs the classification directly using visual image features extracted from the trained network.